Safety use of high frequency oscillatory ventilation in transport of newborn infants affected by severe respiratory failure: preliminary data in central Tuscany - Gilda Belli; Ilaria Dovadola; Elettra Berti; Letizia Padrini; Elisabetta Agostini; Lisa Serafini; Anna Ingargiola; Gabriella Gabbrielli; Elena Sandini; Angelo Azzarà; Serena Catarzi; Maria Luce Cioni; et al. (BMC, 2022)
Abstract Background Neonatal Emergency Transport Services play a fundamental role in neonatal care. Stabilization before transport of newborns suffering from severe respiratory failure is often a challenging problem and some critically ill infants may benefit from High Frequency Oscillatory Ventilation (HFOV) as rescue treatment. In these cases, transition to conventional ventilation for transport may cause a deterioration in clinical conditions. HFOV during neonatal transport has been only exceptionally used, due to technical difficulties. Since May 2018, a new neonatal transport unit is available at the Neonatal Protected Transport Service of the Meyer University Hospital in Florence, equipped with a pulmonary ventilator capable of delivering HFOV. Therefore, we conducted an analysis on patients transferred in HFOV to Neonatal Intensive Care Unit (NICU), in order to evaluate the safety and feasibility of its use during neonatal transport. Methods A retrospective analysis was performed reviewing medical records of the neonates transported by Meyer Children Hospital's Neonatal Transport Service between May 2018 and December 2020, and newborns treated with HFOV during ground neonatal transport were identified. Safety was assessed by the comparison of vital signs, hemogas-analysis values and pulmonary ventilator parameters, at the time of departure and upon arrival in NICU. The dose of inotropes, the main respiratory complications (air leak, dislocation or obstruction of the endotracheal tube, loss of chest vibrations) and the number of deaths and transfer failures were recorded. Results Out of the approximate 400 newborns transported during the analysis period, 9 were transported in HFOV. We did not find any statistically significant difference in vital parameters, hemogas-analytical values and pulmonary ventilator settings recorded before and after neonatal transport of the nine patients' parameters (p > 0,05). No patient required additional inotropes during transport. No transport-related deaths or significant complications occurred during transport. Conclusions The interest of our report is in the possibility of using HFOV during inter-hospital neonatal transfer. As far as our experience has shown, HFOV appears to be safe for the transportation of newborns with severe respiratory failure. Nevertheless, further larger, prospective and multicentre studies are needed to better evaluate the safety and efficacy of HFOV during neonatal transport.